Pendampingan Pembuatan Strategi SWOT untuk Pengembangan Bisnis Albania Coffee & Resto - Mona Tiorina Manurung; Fanniya Dyah Prameswari (JURPIKAT, 2025)
To remain competitive and achieve sustainable growth, business actors must formulate appropriate strategies that align with their business type and potential. One effective strategic approach is SWOT analysis, which assesses a business’s strengths, weaknesses, opportunities, and threats. Albania Coffee & Resto faces challenges in analyzing internal and external factors, making it unprepared both managerially and operationally to handle surges in customer volume. This has led to a decline in service quality, as reflected in customer complaints and negative reviews on Google Review. This Community Service Program was conducted through training in SWOT analysis and assistance in formulating strategies based on the resulting SWOT diagram. Based on the IFAS and EFAS matrices, Albania Coffee & Resto is positioned in Quadrant I, indicating that an aggressive (SO) strategy is the most suitable approach. A satisfaction questionnaire showed increased partner understanding in systematically developing long-term business strategies.